Estrategias de marketing para incrementar las ventas en “modas y comercial la merced” del cantón La Maná provincia de Cotopaxi, año 2022 - Chonillo Macias, Landy Carolina (2023)
The present investigation was focused on the design of digital marketing strategies that will allow to increase the volume of sales of "Modas y Comercial La Merced" located in the Cantón La Maná, Province of Cotopaxi, where through a SWOT analysis it allowed to know the current situation of the company, where it was determined that the main problem is the low volume of sales, this is due to ignorance about the benefits obtained by using digital marketing strategies and those of digital communication media to advertise it, which means that its clients They do not know about the promotions that the products usually have for seasons, as well as the acquisition of new customers. In order to support the project to be developed, it was necessary to investigate in various bibliographic sources, everything related to the research topic, such as: research methodologies, which generated theoretical knowledge as well as the necessary orientation for its elaboration, as well as the data collection instruments. data such as the interview, the survey, based on the Likert scale, allowing the collection of timely information about opinions and suggestions, in order to meet the objectives set. However, for this information to be valid, the Excel computer software was used, where by calculating the Cronbach's Alpha Index, the feasibility of the research project was determined, in relation to the above, the elaboration of a proposal focused on the development of a proposal was chosen as a solution. digital marketing where digital platforms were used such as: Canva, used for the creation of the company logo and advertising designs, Google Site as a website design tool, which is feasible since it locates the company in the Google search engine for last Facebook as a means of dissemination giving optimal results improving not only the volume of sales but the scope of it.